THE EFFECTS OF VOCABULARY AND GRAMMAR MASTERY TOWARDS STUDENT’S SPEAKING SKILL TO THE NINE-YEAR JUNIOR HIGH SCHOOL STUDENTS OF AL - ISLAM KARTASURA - Handayani, Sri (Warmadewa University, 2023)
Abstract: The purpose of this research is to find how the effects of vocabulary and grammar mastery towards student’s speaking skill to the nine-year junior high school students of Al - Islam Kartasura. The reached population of this research is the nine years. The sampling of population consists of 30 students. The research use survey method. The data collected are done by testing the ability of the student in grammar mastery vocabulary mastery and speaking skill. This research is used survey method. This research has three variables. They are grammar mastery (X1) and vocabulary mastery (X2) called as independent variable. Furthermore, speaking skill (Y) called as dependent variable. This research analyzes using multiple linear regressions. This research analyzes using SPSS version 27.00 for windows. The result shows there are any positive correlation. The students who have high vocabulary and grammar score their speaking score are high too. And it has positive correlation. The implication of this research useful for teacher, researcher and another English teacher to applicate this method to their students.